(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Bayan Village on Lombok Island is a tourist village that preserves the traditions of the Sasak-Bayan tribe. The potential of this village lies in the agricultural sector and local products. However, earthquakes and the COVID-19 pandemic have hindered the village’s development. Therefore, rural area planning is needed for sustainable development. One aspect being developed is homestays, although their current use is limited to special interest tourism (research). This study aims to explore the constraints and potential of homestays in the development of Desa Bayan. The research findings show various homestay types with different designs, but they still preserve local traditions. This study also suggests the importance of considering local wisdom and cultural preservation in the development of this village. Thus, this research contributes to developing a tourist village in Desa Bayan, North Lombok, West Nusa Tenggara.